Tryptophan synthase ß subunit 1 affects stomatal phenotypes in Arabidopsis thaliana - Soda, Midori N.; Hayashi, Yuki; Takahashi, Koji; Kinoshita, Toshinori (Frontiers in Plant Science, 2022)
Stomata open in response to several environmental stimuli, such as light and low CO2. Plasma membrane (PM) H+-ATPase in guard cells plays a pivotal role for light-induced stomatal opening. In contrast, stomata close in response to the dark or plant hormone abscisic acid (ABA). However, molecular mechanisms of stomatal movements remain unclear. To elucidate the molecular mechanism of stomatal movements, we performed a genetic screen based on stomatal aperture-dependent weight decrease of detached leaves from EMS-treated Arabidopsis thaliana and isolated a rapid transpiration in detached leaves 2 (rtl2). The rtl2 mutant showed constitutive open-stomata phenotype with lower leaf temperature. ABA had no effect on stomatal aperture in rtl2. The rtl2 mutant also showed increased stomatal density, severe dwarf phenotype with pale green leaves and dark veins. Map-based analysis of the RTL2 locus revealed that the rtl2 mutant possesses a single nucleotide substitution, which induces amino acid substitution Gly162 to Glu in the tryptophan synthase ß subunit 1 (TSB1). The TSB1 encodes an enzyme in tryptophan (Trp) biosynthetic pathway. Amount of TSB1 protein was drastically reduced in rtl2 mutant. A different allele of tsb1 mutant (tsb1-1) also showed constitutive open-stomata phenotype with reduced TSB1 protein as in rtl2. Analyses of test-crossed plants of rtl2 and tsb1-1 showed open-stomata and dwarf phenotypes. These results indicate that a responsible gene for rtl2 is TSB1. We further investigated stomatal phenotype in mutants from Trp biosynthetic pathway, such as wei2-1 wei7-1, trp3-1, and tsb2-1. The trp3-1 mutant showed significant wider stomatal aperture as well as tsb1-1. Trp biosynthetic pathway closely relates to auxin biosynthesis. Then, we investigated auxin responsible genes and found that an expression of AUR3 was up in rtl2. In contrast, auxin had no effect on stomatal aperture in Arabidopsis and the phosphorylation status of PM H+-ATPase in guard cell protoplasts from Vicia faba. In addition, auxin antagonist had no effect on stomatal aperture. Interestingly, tsb1-1 grown under hydroponic culture system showed normal stomatal aperture by exogenously application of Trp. These results suggest that open stomata phenotype in tsb1-1 is due to Trp deficiency but not auxin.